2018
DOI: 10.5194/gmd-11-3427-2018
|View full text |Cite
|
Sign up to set email alerts
|

The microscale obstacle-resolving meteorological model MITRAS v2.0: model theory

Abstract: This paper describes the developing theory and underlying processes of the microscale obstacle-resolving model MITRAS version 2. MITRAS calculates wind, temperature, humidity, and precipitation fields, as well as transport within the obstacle layer using Reynolds averaging. It explicitly resolves obstacles, including buildings and overhanging obstacles, to consider their aerodynamic and thermodynamic effects. Buildings are represented by impermeable grid cells at the building positions so that the wind speed v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The Fortran subroutines for solving the chemical reactions of a given gas-phase chemistry mechanism are generated automatically with the KPP, version 2.2.3 (Damian et al, 2002;Sandu et al, 2003;Sandu and Sander, 2006). KPP creates the code from a list of chemical reactions that represent a certain chemical mechanism.…”
Section: Gas-phase Chemistry Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fortran subroutines for solving the chemical reactions of a given gas-phase chemistry mechanism are generated automatically with the KPP, version 2.2.3 (Damian et al, 2002;Sandu et al, 2003;Sandu and Sander, 2006). KPP creates the code from a list of chemical reactions that represent a certain chemical mechanism.…”
Section: Gas-phase Chemistry Implementationmentioning
confidence: 99%
“…KPP offers a variety of numerical solvers for the system of coupled ordinary differential equations describing the chemical reactions. Tests comparing the performance of the Rosenbrock solvers implemented in KPP have shown that the use of the most simple Rosenbrock solver, Ros-2, did not lead to significantly different results than the use of the Rosenbrock solvers with higher orders (Sandu and Sander, 2006;Jöckel et al, 2010). Therefore, the Ros-2 solver was chosen as the default solver for the PALM-4U chemistry model.…”
Section: Gas-phase Chemistry Implementationmentioning
confidence: 99%
“…It is our goal to avoid such assumptions keeping in mind that processes that are advectively driven by flows in climate and weather applications have divergence, do not have mean zero and do not exhibit a scale separation. Yet, they dominate many parameterized processes that can manifest in precomputed diffusion coefficients coming from other sources, e.g., see [33,34] for a simulation environment of urban areas and canopies.…”
Section: Motivation and Overviewmentioning
confidence: 99%
“…Masson (2006) describes several types of UCM according to their degree of complexity and realism, and Grimmond et al (2010Grimmond et al ( , 2011 further classify each physical component of these schemes, underlining the need for data to describe the city. When going to the microscale, individual buildings are explicitly resolved by Obstacle Resolving Models (ORMs) (Krayenhoff et al, 2015;Resler et al, 2017;Salim et al, 2018). These ORMs create a high demand for detailed input data.…”
Section: Brief Overview Of Urban Atmospheric Modellingmentioning
confidence: 99%